2014
DOI: 10.1007/s11096-014-0046-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction-related hospitalisations among patients with heart failure at two hospitals in the United Arab Emirates

Abstract: ADR-related hospitalisations account for 6.7 % of admissions of HF patients to cardiac units, one-third of which are preventable. Number of medications taken by HF patients is the only predictors of ADR-related hospitalisations. Diuretic induced volume depletion, and sodium and water retention caused by thiazolidinediones and NSAIDs medications are the major causes of ADR-related hospitalisations of HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(48 reference statements)
1
8
1
Order By: Relevance
“…The majority of preventable HF hospitalizations, deaths and increased health care cost are due to poor adherence to the use of approved evidence-based medications [ 24 ]. It has been reported that about 17% of HF patients may experience adverse effects of their medication and ADR-related hospitalizations account for 6.7% of admissions of HF patients to cardiac units [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of preventable HF hospitalizations, deaths and increased health care cost are due to poor adherence to the use of approved evidence-based medications [ 24 ]. It has been reported that about 17% of HF patients may experience adverse effects of their medication and ADR-related hospitalizations account for 6.7% of admissions of HF patients to cardiac units [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Antithrombotics are frequently prescribed to older people and patients with cardiovascular problems, who are more prone to ADRs. 35 The risk of major cardiovascular events like cerebrovascular accidents and myocardial infarctions is related to many factors that are also risk factors for dementia, including age and cardiovascular disease. 36 Antithrombotics such as aspirin are prescribed to people with dementia for reducing the risks of major cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective method identified more cardiovascular ADRs (mainly caused by diuretics and renin‐angiotensin system inhibitors), largely hypotension/orthostatic hypotension/syncope, than the administrative coding method. In another study involving prospective chart review by clinical pharmacists in heart failure patients, the most frequent drugs causing ADR‐related hospital admissions were diuretics and non‐steroidal anti‐inflammatory drugs causing electrolyte disturbances and heart failure exacerbation, respectively …”
Section: Discussionmentioning
confidence: 99%